Analysis of Agricultural Production Potential and Enhancement Strategy in the Qaidam Basin Based on the Agro-Ecological Zone Method - Yu, Hui; Huang, Min; Zhao, Tao; Wang, Jianping; Li, Zihan; Chen, Dianpeng; Li, Pengshan; Luo, Yong; Wang, Haoyu; Jing, Zhao; Mou, Dongyang; Zhang, Dan; et al. (Frontiers in Environmental Science, 2022)
The Qaidam Basin has an arid plateau continental climate, with climatic factors strongly influencing agricultural production potential. In the present study, the agro-ecological zone method was applied to study the effects of rainfall, temperature and soil on crop yield, with climatic factors as the main common influencer. By assessing the land production potential, suitable zones for grain production were identified in the Qaidam Basin, and the reasonable current input level was determined, thus, evaluating the population carrying capacity. Strategies for improving crop productivity in these regions were proposed to provide a basis for decision-making by the local government. The results showed that: (1) The photosynthetic and light-temperature production potential was high in Mangya city and the autonomous region; however, the climate production potential was low in Golmud city and the eastern part of Mangya city. After correction based on soil availability, the land production potentials of spring wheat and highland barley were greatly attenuated, and only 15.85% and 16.74% of the photosynthetic production potential, respectively. (2) The current population carrying capacity of the land resources is 595,900 people, which is in a state of human–food balance when the correction coefficient of artificial input is approximately 1.1. If the artificial input can be strengthened to achieve a correction coefficient of 1.2, the population carrying capacity could reach 676,100 people. (3) The suitable area for agricultural production was mainly located in the northeast and west of the Qaidam Basin. These areas can be used as a backup arable land resource. The temperature increase leading to evaporation increase negatively affected the yield per unit area of grain crops in Qaidam Basin. Strengthening water-saving irrigation technology and improving the utilisation rate of chemical fertilisers are good enhancement strategies for the green-oriented agricultural technology system, which would help improve the agricultural productivity potential in the Qaidam Basin.